Probiotic/prebiotic correction for adverse effects of iron fortification on intestinal resistance to Salmonella infection in weaning mice. Issue 2 (22nd January 2018) - Lin, Feifei; Wu, Haohao; Zeng, Mingyong; Yu, Guangli; Dong, Shiyuan; Yang, Huicheng
Abstract : Our study provides experimental evidence for the increased diarrhea risk upon iron fortification with high pathogen load, and demonstrates that probiotic or prebiotic supplementation can be used to eliminate the potential harm of iron fortification on gut health. Abstract : Iron fortification has been associated with a modest increase in diarrhea risk among children. Herein, we investigate the correction for this unwanted side effect with probiotic/prebiotic supplementation in weaning mice. Iron fortification with 250 ppm and 500 ppm ferrous sulfate for 30 days significantly increased the species richness of the mouse gut microbiota compared to controls. The 500 ppm-FeSO4 diet caused a significantly decreased abundance of potentially beneficial Lactobacillus . During infection with the foodborne pathogen Salmonella enterica serovar Typhimurium ( S . Typhimurium), mice on the 500 ppm-FeSO4 diet showed earlier appearance of poisoning symptoms, higher rates of weight and appetite loss, and lower survival rates, all of which were effectively reversed by supplementation with a probiotic ( Lactobacillus acidophilus ) or a prebiotic (inulin) for 7 days before infection. Iron fortification with 500 ppm ferrous sulfate also increased fecal shedding and spleen and liver load of viable S . Typhimurium, suggesting its promoting effect on pathogen colonization and translocation, and this negative effect was found to be well corrected by supplementation with Lactobacillus acidophilus or inulin. Light and transmission electron microscopic observation on the ileal villus structure revealed the histopathological impairment of the intestine by iron fortification with both 250 ppm and 500 ppm ferrous sulfate, and the intestinal lesions were markedly alleviated by supplementation with Lactobacillus acidophilus or inulin. These results provide experimental evidence for the increased diarrhea risk upon iron fortification with high pathogen load, and demonstrate that probiotic or prebiotic supplementation can be used to eliminate the potential harm of iron fortification on gut health.